2005
DOI: 10.1074/jbc.m504894200
|View full text |Cite
|
Sign up to set email alerts
|

A Combinatorial Code for the Interaction of α-Synuclein with Membranes

Abstract: Considerable genetic and pathological evidence has implicated the small, soluble protein ␣-synuclein in the pathogenesis of familial and sporadic forms of Parkinsons disease (PD). However, the precise role of ␣-synuclein in the disease process as well as its normal function remain poorly understood. We recently found that an interaction with lipid rafts is crucial for the normal, pre-synaptic localization of ␣-synuclein. To understand how ␣-synuclein interacts with lipid rafts, we have now developed an in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
162
3
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(174 citation statements)
references
References 48 publications
8
162
3
1
Order By: Relevance
“…Early studies showed that the binding of AS to extracts of brain tissue lipid membranes did not require the presence of other proteins (27), and therefore AS also binds readily to artificial membranes (4,(27)(28)(29)(30). Because the lipophilic N-terminal part of AS is positively charged, the protein has a preference for anionic membranes (28).…”
mentioning
confidence: 99%
“…Early studies showed that the binding of AS to extracts of brain tissue lipid membranes did not require the presence of other proteins (27), and therefore AS also binds readily to artificial membranes (4,(27)(28)(29)(30). Because the lipophilic N-terminal part of AS is positively charged, the protein has a preference for anionic membranes (28).…”
mentioning
confidence: 99%
“…These changes in glycosphingolipids may particularly affect lipid raft function by interfering with the sorting and trafficking of proteins and lipids associated with the rafts. Notably, α -synuclein is localized in some of the lipid rafts in neuronal cells (Fortin et al , 2004 ;Kubo et al , 2005 ). Therefore, it is speculated that GBA1 mutation-induced lipid changes may alter the interaction between lipid microdomains and α -synuclein.…”
Section: Lipid Alterations and Accumulationmentioning
confidence: 99%
“…Alterations in membrane lipid composition are thought to be an important factor affecting the interaction between α -synuclein and lipid membranes (Kubo et al , 2005 ). Changes in lipid composition may occur through oxidative modifications or metabolic alterations ( O ' Donnell et al, 1999 ;Mosca et al , 2011 ).…”
Section: Lipid Alterations and Accumulationmentioning
confidence: 99%
“…Biskup et al (2006) also reported the presence of LRRK2 in membrane structures, such as lysosomes, endosomes, transport vesicles and mitochondria. In this regard it is interesting to note that a-synuclein is also expressed in the presynaptic membranes and lipid rafts (Fortin et al 2004;Kubo et al 2005).…”
Section: ; Canet-avilesmentioning
confidence: 99%
“…The mutant a-synuclein has increased tendency for self-aggregation (El Agnaf et al 1998). a-Synuclein is mainly located in the lipid raft in membranes (Fortin et al 2004;Kubo et al 2005) and this localization appears to be important in the trafficking of a-synuclein and its final localization in presynaptic and synaptic vesicular membranes.…”
Section: Dysfunction Of Protein Degradation In Pdmentioning
confidence: 99%